Novel Traditions of Library as Societal Culture Conservation - Wiji Suwarno (Institut Agama Islam Negeri Salatiga, 2017)
Library is not only a space for displaying books, but there are many important values within. The paradigm of library has been shifted from books oriented into user oriented meaning library is as sources of information. Besides that, library plays its roles as an institution of cultural heritage conservators in maintaining cultural values, and revitalizing the tradition. In this technology era, this article tries to explain the interesting phenomena in the libraries of the State Institute for Islamic Studies (PTKIN) in Indonesia concerning the history of the emergence and development of such novel traditions including Online Research Skill (ORS) and Writing Skill (RS).